NEUROSTEROID, NATURAL AND ANABOLIC STEROIDS: PHYSIOLOGICAL, IMMUNOLOGICAL AND HISTOPATHOLOGICAL STUDY ON HYPERLIPIDAEMIC ALBINO RATS - KHIDER, QAIS L.; SOFI , AMAD M. S.; AL-BARWARY, MALIKA K. N. (Journal of Duhok University, 2023)
Neurosteroids are steroids that include endogenous steroids that the nervous system produces, and they function as neurotransmitters or neuromodulators. steroid hormones are chiefly produced in the adrenal glands and have a pivotal role in the regulation of many physiological actions in the body. An anabolic steroid, which is an artificial compound, has similar effects to testosterone. This study aimed at distinguishing between the roles of neurosteroid, natural steroid, and anabolic synthetic steroids by investigating the effects of some physiological, immunological, and histopathological on various target organs such as the Kidney, liver and spleen in hyperlipidemic rats. In order to achieve these aims, we randomly divided 50 male albino rats into five equal groups. The first group, which was fed on standard diet and injected subcutaneously with 0.5 ml of normal saline, was used as the control group, while the second group, which served as the hyperlipidemic control group was fed a high fat diet. The third group, hyperlipidemic rats, were orally administrated with DHEA (as a neurosteroid, 17.2mg/kg/day), the fourth group, hyperlipidemic rats, were subcutaneously injected with hydrocortisone (as a natural steroid, 26.1mg/kg/day). Finally, the fifth group of hyperlipidemic rats were intramuscularly injected with Sustanon (as an anabolic steroid, 66.9 mg/kg/week). The study has found that hyperlipidemic rats showed hematological parameters and interleukin IL-2 improvements with DHEA, fasting blood sugar and body weight with Sustanon and a lipid profile with both hydrocortisone and Sustanon, Renal function was almost deteriorated in all treated groups, and finally there were various alterations in the histopathological examination of kidney, liver and spleen. Finally, the study has come up with the following conclusions: DHEA administration can improve immunity and ameliorate tissue damage in the spleen. Hydrocortisone may improve the lipid profile, though it has negative effects on immunity and tissue health. Sustanon has positive effects on blood glucose and lipid profile; however, its effects on immunity are not clear enough